Thyrotropin Regulates eNOS Expression in the Endothelium by PGRN Through Akt Pathway - Jiang, Fengwei; Wang, Haoyu; Bao, Suqing; Zhou, Haicheng; Zhang, Yuanyuan; Yan, Yumeng; Lai, Yaxin; Teng, Weiping; Shan, Zhongyan (Frontiers in Endocrinology, 2018)
To investigate the expression of endothelial nitric oxide synthase (eNOS) and nitric oxide (NO) in the aorta of subclinical hypothyroidism (SCH) rat model. The mechanisms underlying thyrotropin (TSH) affecting eNOS and PGRN expression in human umbilical vein endothelial cells (HUVECs) cultured in vitro were investigated. In the current study, SCH rat models were established by the administration of L-T4 injection after thyroidectomy in Wistar rats, as opposed to that in the normal and clinical hypothyroidism (CH) groups. The concentrations of NO (pmol/μL) in the SCH and CH groups were significantly lower than that in the normal group (40.8 ± 7.6 and 32.9 ± 10.8 vs. 51.2 ± 12.1, P < 0.05). However, the expression level of eNOS is increased significantly (P < 0.05) in both SCH and CH groups; a similar result was observed for the PGRN protein. In cultured HUVECs, TSH can also up-regulate the expression of eNOS; however, it is accompanied by a reduced concentration of NO and increased level of superoxide anion, thereby indicating uncoupled eNOS. As eNOS is increased, we found that Akt in HUVECs were upregulated by TSH, as well as PGRN expression. While inhibiting the expression of PGRN in HUVECs using siRNA, the expression of eNOS, as well as Akt were also inhibited. In conclusion, SCH can induce vascular endothelial dysfunction in rats, and PGRN participated in the process of TSH-induced expression of Akt/eNOS in the endothelium.